Impact of financial inclusion on poverty through Islamic microfinance in Mauritania - Maouloud, Vatimetou Mokhtar; Kassim, Salina; Othman, Anwar Hasan Abdullah (IGI Global, 2021)
Poverty is a severe problem, particularly in third world countries. Since reducing poverty is the first goal of Sustainable Development Goals of the United Nations, it is the concern of numerous organizations and governments. This chapter is a conceptual paper that discusses the effectiveness of microfinance in eradicating poverty. The main purpose of this chapter is to present the current situation of poverty in Mauritania and the prospect to alleviate it through Islamic microfinance and financial inclusion. It also attempts to propose new suggestions for the Mauritanian government to alleviate poverty and increase people's wellbeing. It has been concluded that Islamic microfinance can reduce poverty in Mauritania. Thus, this research recommends policymakers and managers of Islamic microfinance to enhance the outreach of microfinance institutions to reach a large segment of vulnerable people. This study is among the pioneers in the field of Islamic microfinance in Mauritania, so it fills up this gap in the literature and adds new theoretical discussion to the topic worldwide.